PENGARUH MODIFIKASI DOVETAIL-CROWN TIP PADA ROTOR TERHADAP PRESSURE RATIO KOMPRESOR AKSIAL MULTISTAGE - Ibnu Samsul Kurniawan; Setyo Nugroho; Prima Dewi Permatasari (PROSIDING SNAST, 2018)
Compressors are one type of turbomachinery to add energy of fluid and move fluid from one location to another. Axial compressor on gas turbine used to compress fluid to get the required pressure increase. Multiple-stage axial compressor have a high level performance, that is 70-80%. Compressor performance is related with energy utilization, the greater the energy loss, the lower the compressor performance. The biggest energy loss is caused by aerodynamic loss, stall phenomenon and tip clearance. Gap between casing and rotor can cause secondary flow, leakage flow and boundary scrapping. These three streams can cause energy losses and affect the pressure ratio produced by the compressor. One way to get better performance with add dovetail-crown tip modification on the rotor, with the aim of reducing energy loss on the tip clearance. Modification of dovetail-crown tip on the rotor that is, the airfoil profile extended 75% of tip clearance compressor, then given a square gap along the chord with a/b ratio of 1:3. The axial compressors that become the testing system have parameters: 0.5 degree reaction, three stage, stagger angle 24 °, NACA 65- (19) -10 blade profile. Based on the results, the addition of a modified tip blade in the form of a dovetail-crown tip can reduce energy losses by presenting an average reduction in energy losses of 11.9%. The results also show that the use of dovetail-crown tip modification can increase the compressor pressure ratio with an average percentage increase of 0.0219%.